An Analysis of Pronouns Used in Selected International Journal Articles: Exploring Authors’ Flexibility and Consistency - Rumintang Harianja; Ratih Saltri Yudar; Susy Deliani; Mutia Sari Nursafira; Budianto Hamuddin (REiLA : Journal of Research and Innovation in Language, 2020)
The aim of this study is to identify the pronouns used in journal articles in terms of numbers and familiarity. The total of the journal in this research was 21 articles taken from the current issue 2018 from three different fields i.e., Education, Medics and Engineering. Its selected conveniently due to its unique and fame as a discipline. In collecting the data, the researcher accessed the journals indexed in science direct. The analysis showed that the writer in these three international journals commonly used several pronouns interchangeably. However, some articles consistently used only one pronoun, which were recorded at different in different sections in the journal article. The data then coded and transcribed to ease the analysis in this researcher. As a result of the analysis, it was found out that the data showed 19 kinds of pronouns in total were used in these three different fields. These results showed us that the pronoun usage in a scientific article from these three different fields varies with options of different pronouns. The pronoun seems used to help an impact of imposition and showing politeness or quality of the articles.